General geology and structural analysis in Kampung Sungai Sam and its surroundings in Kuala Krai, Kelantan. - Nurin Elisha Zainurin (2016)
Geological mapping has been used as the process of making observation and interpret the geology in the ﬁeld. Stereonet and statistical technique has been used in order to analyze the structural features in terms of compressional and tensional force. In order to know the direction of major trends, the reading of strikes and dip directions were taken within the outcrops. Interpretation of lineament and structural analysis has been done to study the causes of these deformation features in the study area. The study area is located at Kampung Sungai Sam, Kuala Krai, Kelatan. The study area covered a part of Lebir fault which is along Lebir valley. The aim of this study was to prepare and update the general geological map of Lebir valley and to analyze and interpret structural features including direction of fractures. There are three phases of geological mapping process which is preliminary research, collection of data and report writing including the preparation of thin section in mineral examining. The detailed general geology, geomorphology, and lithostratigraphy of study area is required to produce geological map. The study area is located in igneous and elastic sedimentary lithology. Granites cover 70 percent of the lithology map while the rest comprising with minority of sandstone. From the previous study, the age of rocks in central belt which includes Lebir fault, is to be Jurassic- Cretaceous age. Besides that, to analyzed the structural features, statistical technique including rose diagram has been done. Both positive and negative lineament together with fractures show the major trend towards Northern-Southern direction proving that all these deformation due to the regional force. The action of Lebir fault produce energy to the rocks and form huge amount of fractures.